Modelo de precificação do seguro de crédito à exportação para o mercado brasileiro - Pancevski, Predrag (2005)
This work addresses the elements that determine the acceptance of export credit insurance in the Brazil from the insurance companies’ viewpoint as well as the exporting companies´ which are the potential clients of this product. After the presentation of the relevant economic theories that guide the credit insurance, and supported by the analyzed acceptance criteria, we propose an original risk pricing model. This model, which is adjusted to the Brazilian market and based on statistical data collected by us since 1997 when the credit insurance runned by private companies started in Brazil, aims to meet the needs of the insurance industry for a tool well tuned up to the national reality.